1996
DOI: 10.1093/hmg/5.4.451
|View full text |Cite
|
Sign up to set email alerts
|

Xist expression from an Xist YAC transgene carried on the mouse Y chromosome

Abstract: We have constructed mouse transgenic lines carrying a YAC clone encompassing the Xist gene in order to investigate the factors influencing Xist expression and the initiation of X-inactivation. Two transgenic lines were derived, one carrying four copies integrated at an autosomal site and a second line carrying four copies integrated at a single site on the Y chromosome. Xist expression was not observed in mice carrying the autosomal insertion. However, Xist expression from the Y-inserted transgenes was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 26 publications
0
12
1
Order By: Relevance
“…We obtained six independent Tg lines. In contrast to the lack of phenotype observed previously with YAC Tgs (39)(40)(41), intriguing phenotypes were observed in five of the six hemizygous transgenic lines, here named Tg2080, Tg2082, Tg2086, Tg2087, Tg2091, and Tg2092 (Fig. 1B).…”
Section: Resultscontrasting
confidence: 82%
“…We obtained six independent Tg lines. In contrast to the lack of phenotype observed previously with YAC Tgs (39)(40)(41), intriguing phenotypes were observed in five of the six hemizygous transgenic lines, here named Tg2080, Tg2082, Tg2086, Tg2087, Tg2091, and Tg2092 (Fig. 1B).…”
Section: Resultscontrasting
confidence: 82%
“…Strangely, the transgenic lines reported previously did not exhibit any abnormalities (12)(13)(14), suggesting that they are incapable of maintaining Xicdependent repression autosomally. In the report from Sun et al, the smaller BAC transgenes confer several phenotypes, including sterility, indicating that they contain all of the necessary sequences to establish and faithfully maintain repression of the neighboring genes.…”
mentioning
confidence: 74%
“…Indeed, it has been recently reported that Xist introduced in an autosome is sufficient by itself for X inactivation in cis, suggesting that Xic is composed of the Xist gene alone (Herzing et al, 1997) and that the Xist gene alone plays a direct role in X-chromosome choosing (Marahrens et al, 1998) and initiation of X inactivation through Xist RNA stabilization (Panning et al, 1997;Sheardown et al, 1997). However, further studies are needed to confirm the above findings, because similar experiments where Xic segments were introduced onto autosomes did not result in Xist induction (Heard et al, 1996;Matsuura et al, 1996).…”
mentioning
confidence: 86%